A new species of Admesturius Galiano, 1988 from north Chile (Araneae: Salticidae: Amycoida) - Bustamante, Abel A. (2014)
A new species of Admesturius Galiano from the Atacama-desert is decribed and illustrated. This species is the northernmost record of the genus in Chile.